Decreased Self-Appraisal Accuracy on Cognitive Tests of Executive Functioning Is a Predictor of Decline in Mild Cognitive Impairment - Scherling, Carole S.; Wilkins, Sarah E.; Zakrezewski, Jessica; Kramer, Joel H.; Miller, Bruce L.; Weiner, Michael W.; Rosen, Howard J. (Frontiers in Aging Neuroscience, 2016)
Objective: Mild cognitive impairment (MCI) in older individuals is associated with increased risk of progression to dementia. The factors predicting progression are not yet well established, yet cognitive performance, particularly for memory, is known to be important. Anosognosia, meaning lack of awareness of one’s impaired function, is commonly reported in dementia and is often also a feature of MCI, but its association with risk of progression is not well understood. In particular, self-appraisal measures provide an autonomous measure of insight abilities, without the need of an informant. Method: The present study examined the utility of self-appraisal accuracy at baseline for predicting cognitive decline in 51 patients using an informant-free assessment method. Baseline task performance scores were compared to self-assessments of performance to yield a discrimination-score (DS) for tasks tapping into memory and executive functions. Results: Linear regression revealed that a larger DS for executive function tasks in MCI predicted functional decline, independent of age, education, and baseline memory and executive task scores. Conclusions: These findings indicate that objective estimates of self-appraisal can be used to quantify anosognosia and increase predictive accuracy for decline in MCI.